2019
DOI: 10.1073/pnas.1818501116
|View full text |Cite
|
Sign up to set email alerts
|

High-dimensional representation of texture in somatosensory cortex of primates

Abstract: In the somatosensory nerves, the tactile perception of texture is driven by spatial and temporal patterns of activation distributed across three populations of afferents. These disparate streams of information must then be integrated centrally to achieve a unified percept of texture. To investigate the representation of texture in somatosensory cortex, we scanned a wide range of natural textures across the fingertips of rhesus macaques and recorded the responses evoked in Brodmann’s areas 3b, 1, and 2. We foun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 62 publications
(106 reference statements)
3
68
0
Order By: Relevance
“…Indeed, recent large-scale electrophysiology and imaging studies have found high dimensional (>100) representations within a brain region, with neural activity often representing small aspects of behavior (e.g. facial twitches, limb position, etc; Stringer et al, 2019a, 2019b; Lieber and Bensmaia, 2019). However, while this high dimensionality of neural representations is great for capturing the fullness of an experience, its complexity presents a problem for cognitive control.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent large-scale electrophysiology and imaging studies have found high dimensional (>100) representations within a brain region, with neural activity often representing small aspects of behavior (e.g. facial twitches, limb position, etc; Stringer et al, 2019a, 2019b; Lieber and Bensmaia, 2019). However, while this high dimensionality of neural representations is great for capturing the fullness of an experience, its complexity presents a problem for cognitive control.…”
Section: Discussionmentioning
confidence: 99%
“…Human and macaque hands show very similar patterns of cutaneous innervation (Darian-Smith and Kenins, 1980;Johansson and Vallbo, 1979;Paré et al, 2003) and the tactile nerve fibers in the two species exhibit nearly identical response properties (Johansson et al, 1982;Phillips et al, 1992). Human texture perception can be successfully predicted by the responses of macaque nerve fibers (Blake et al, 1997;Connor and Johnson, 1992;Connor et al, 1990;Lieber et al, 2017;Weber et al, 2013) and cortical neurons (Bourgeon et al, 2016;Lieber and Bensmaia, 2019).…”
Section: Validity Of the Macaque Model For Human Texture Perceptionmentioning
confidence: 99%
“…Next, we examined the extent to which neuronal responses could account for the well-documented speed-tolerance of texture perception (Boundy-Singer et al, 2017;Lederman, 1974;Meftah el-M et al, 2000). To this end, we tested the hypothesis that perceived roughness is determined by the population firing rate in somatosensory cortex (Burton and Sinclair, 1994;Lieber and Bensmaia, 2019) using a previously published set of roughness ratings from human subjects. First, we regressed roughness ratings -obtained from human subjects -on to the population firing rate evoked when textures are scanned across the skin at 80 mm/s ( Figure 3A)(cross validated R 2 , peripheral: 0.81, cortical: 0.77).…”
Section: Cortical Responses Can Explain Speed-tolerant Texture Percepmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuronal representation of sensory information is highly complex [11], and the ability to selectively recruit neuronal populations proximal to the electrode by varying pulse amplitude, frequency, or polarity, could provide the ability to stimulate neural activity that matches physiological response patterns [12][13][14][15][16][17][18][19][20][21][22][23][24]. For example, neuronal adaptation is a common response to sustained stimuli and is believed to allow the brain to better respond to transient stimuli [25].…”
Section: Introductionmentioning
confidence: 99%